Incentives and disincentives to participation by clinicians in randomised controlled trials - Rendell, J; Merritt, R; Geddes, J (2007)
Background: Patients and clinicians need reliable, up-to-date information from randomised controlled trials (RCTs) on the costs and benefits of treatments. Recruitment difficulties arise when clinicians do not invite patients to participate in trials. Objectives: Primary: to assess the evidence for the effect of disincentives and incentives on the extent to which clinicians invite eligible patients to participate in RCTs of healthcare interventions. Secondary: to assess the evidence in relation to stated willingness to invite participation. Search strategy: 1. The Cochrane Methodology Register and Cochrane Database of Methodology Reviews were searched in May 2006 and Cochrane Central Register of Controlled Trials, National Research Register and ClinicalTrialsGov in April 2005. 2. EMBASE, MEDLINE, CINAHL, PsycINFO and AMED were searched in April 2005. 3. Reference lists of included studies were checked. Selection criteria: Studies exploring the effect of (dis)incentives on clinicians' views and recruitment-related activity. Data collection and analysis: The information about included studies was insufficient for a full assessment of quality. Data on (dis)incentives were extracted and association with recruitment tested. Main results: No RCTs of interventions were identified. Eleven observational studies were included - two medical records reviews, one matched pair study, one clinician interview study, two studies documenting clinicians' decisions and five postal surveys. Three measures of recruitment were used, invitation to participate, entry into RCT and reported entry to RCT. Five studies explored the effect of patient characteristics. The effect of age and prognosis varied between trials. Six studies considered the association between clinicians' views and recruitment. Clinicians who agreed to participate because they were acquainted with the researchers were less likely to participate than those otherwise motivated (1 study, 2-sided p = 0.04 Fisher's exact test) and (Odds Ratio [OR] 0.4, 95% Confidence Interval [CI] 0.2 to 0.9, 1 study). Clinicians who had recruited were more likely to report some difficulties including "trials involve extra work" (OR 92.94, 95% CI 4.54 - 1902.11; p 0.01, 1 study) and "inviting patients to participate is embarrassing" (chi-square 15.55, df = 1, p < 0.0001, 1 study). The effect of the need to discuss clinical uncertainty was unclear but concern that the doctor-patient relationship would be adversely affected by participation was a deterrent (chi-square = 7.25, df = 1, p = 0.007, 1 study). Authors' conclusions: The impact of factors varied across studies. Researchers need to be aware that aspects of the design and conduct of trials can affect clinicians' willingness to invite patients to participate. Further research is needed. Copyright © 2008 The Cochrane Collaboration. Published by John Wiley and Sons, Ltd.